how do you write 40% as a fraction or mixed number in simplest form

Answers

Answer 1
Fraction = 2/5
Hope this helps
Answer 2
it goes to 40/100 then reduce it to 4/10 and finally 2/5

Related Questions

which number is equivalent to 0.3

1/3

33/100

5/6

2/3

Help plz asap!!!

Answers

None of them are equivalent to 0.3, unless it's 0.3 with a bar over the 3, in which case the answer is 1/3.

Solution:

Convert all the numbers to decimal form;

1/3 = 0.3 (where 3 is recurring)

33/100 = 0.33

5/6 = 0.83 (where 3 is recurring)

2/3 = 0.6 (where 6 is recurring)

The correct choice is  1/3 since its the only choice that don't give a limitation on rounding up the decimal value to 1 decimal place.


Which of the following represents a function?

(3, 4), (-3, 2), (3, 8), (5, 5)

(2, 3), (4, 3), (-2, -3), (-4, -3)

(-1, 2), (-2, 1), (-1, -2), (-2, -1)

(5, 1), (5, 2), (5, 3), (5, 4)

Answers

Is there a none option? if not then it has to be B.
the second one because it pass the vertical line test

50+5y-20=14y-12-2y y=

Answers

Hey there!

Equation given :

50 + 5y - 20 = 14y - 12 - 2y

Combining like terms :

30 + 5y = 12y - 12

Adding 12 on both sides :

42 + 5y = 12y

Subtracting 5y on both sides :

7y = 42

Dividing by 7 on both sides :

y = 6

The value of y is 6.

Hope my answer helps!!

A restaurant sells 330 sandwiches each day. For each $0.25 decrease in price, the restaurant sells about 15 more sandwiches. How much should the restaurant charge to maximize daily revenue? What is the maximum daily revenue? Each sandwich is 6$ beforehand...

Answers

Answer:

The value that optimizes this inequality is x = 1, since it represents the vertex of the parabola. Therefore, $ 0.25 is the price that must be discounted to maximize revenues

With x = 1 the value of the new income will be = $ 1983.75

Step-by-step explanation:

Revenue with the current sale price is:

6 * 330 = $ 1980

Let's call x the number of times the price of a sandwich decreases, that is, if x = 1 then the price of the sandwich decreases by $ 0.25

Then, the price would be:

Price = (6-0.25x)

Then, if the price is decreased by a factor of x, then the number of sandwiches sold will increase by a factor of 15x. Therefore the number of clients will be:

Sale = (330 + 15x)

Now we need an equation for income. The income will be equal to the sale price, for the number of sandwiches sold

Income = price * sale

Income = (6-0.25x) (330 + 15x)

In order for this restaurant pricing model to be profitable, the revenues with the new sale price must be greater than the revenues with the sale price of $ 6. So:

New income> current income.

[tex](6-0.25x) * (330 + 15x)> 330 * 6\\ (6-0.25x) * (330 + 15x)> 1980[/tex]

The left side of the inequality represents a parabola:

[tex]-3,750x ^ 2 + 7.5x + 1980> 1980[/tex]

The value that optimizes this inequality is x = 1, since it represents the vertex of the parabola. Therefore, $ 0.25 is the price that must be discounted to maximize revenues

The attached image shows the region that satisfies the proposed inequality and the vertex of the parabola:

[tex]x = \frac{-b}{2a}[/tex]

With x = 1 the value of the new income will be = $ 1983.75

How does buying items in bulk usually help a consumer?

A.
The consumer gets better quality.
B.
The consumer pays less per item.
C.
There are fewer items to store.

Answers

B) The consumer pays less per item.

If a bag of chips cost .15, but if 20 bags cost $2, you are saving $1.

Hope I helped!

Good Luck!

Answer:

B.) The consumer pays less per item

Step-by-step explanation:

If you buy items in bulk, you will pay a higher total price but a lower price per item. For instance, buying a package of four rolls of paper towels will usually be cheaper than buying one roll four times.

the length of a rectangle is 3 times the width. the area is 27 square centimeters. What is the length?

Answers

Hello.

The answer is: 24

length=3*width, this can be written as 3w

area=27 sq cm

Formula for the area of a rectangle=27 (area)= 3w (length) * w (width)

27=3w^2

then divide both sides by 3: 9=w^2

take the square root of both sides to get: w=3

Now that we know what the width is, we can substitute that and find the length: 3w= 3*3=24

have a nice day

Factor the following completely.

r^2 - 14r -50

Answers

you can't factor it at all

ANSWER FAST PLEASE Which is a reasonable first step that can be used to solve the equation 4x+3(x+2)=5(2x-3)

Answers

Distribute 3 to x + 2 and distribute 5 to 2x - 3

27x$42 answer to the problem

Answers

$1134 is the correct answer

27•42= 1134

27 x $42 = $1,134

Hope this helps you

-AaronWiseIsBae

Could someone give me step by step instructions PLEASE! Thanks so much!!

Answers

x=2

(2X-8.6)/2=-2.3

multiply both sides by 2 to gte rid of the denominator

2x-8.6= -4.6

add 8.6 to both sides

2x=4

x=2

Isolate the x. Note the equal sign. What you do to one side, you do to the other.

First, multiply 2 to both sides

(2x - 8.6)/2(2) = -2.3(2)

2x - 8.6 = -4.6

Isolate the x. First, add 8.6 to both sides

2x - 8.6 (+8.6) = -4.6 (+8.6)

2x = -4.6 + 8.6

2x = 4

Next, to isolate the x, divide 2 from both sides

2x/2 = 4/2

x = 4/2

x = 2

2 is your answer for x

~Rise Above the Ordinary

given that g(x)=x^2-3x-6, find (gog)(-3)

Answers

(gog)(-3) basically means g(g(-3)).

g(-3) = (-3)^2 - 3(-3) - 6

g(-3) = 12

g(12) = 102

So the answer is 102.

There is a triangle and the first side is 3m , The second side is 4 - m , and the third side is 2m - 1. What expression would represent the perimeter of the triangle?

Answers

perimeter = 4m + 3

the perimeter is the sum of the 3 sides of the triangle, thus

perimeter = 3m + 4 - m + 2m - 1 = 4m + 3


Answer: 4m + 3


Step-by-step explanation:

This is because the perimeter of a triangle is the same as adding all of its sides.

3m+(4-m)+(2m-1)

Group like terms:

(3m-m+2m) + (4-1)

Then combine like terms to get your final answer of:

4m + 3


20,21,22,23 are the ones I need help on if you can help I’ll mark you as super smart !!!

Answers

Answer:

20) 10x - 10 = 120

10x = 130

x = 13

21) 6x + 10 + 8x + 2 = 180

14x + 12 = 180

14x = 168

x = 12

22) 5x + 5x + 6 + 94 = 180

10x + 100 = 180

10x = 80

x = 8

23) 2x + 3 + 4x + 1 = 124

6x + 4 = 124

6x = 120

x = 20

The difference between two numbers is 15. If 8 is added to twice the greater number, the result is 4 less than 3 times the lesser number. Find the two numbers.

Answers

Answer:


Step-by-step explanation:

Let [tex] x[/tex] be the greater number and [tex] y [/tex] be the smaller number. We know that their difference is 15, so we have

[tex] x-y=15 [/tex]

Then, we have the following information: if we add twice the greater (2x) and 8 (2x+8), the result is 3 times the lesser (3y) minus four (3y-4). So, we have

[tex] 2x+8 = 3y-4 \iff 2x-3y = -12 [/tex]

So, we have the follwing system:

[tex] \begin{cases} x-y=15\\2x-3y = -12\end{cases} [/tex]

From the first equation, we can derive [tex] x = y+15 [/tex], and substitute this expression in the second equation to get

[tex] 2(y+15)-3y = -12 \iff 2y + 30 -3y = -12 \iff -y = -42 \iff y = 42 [/tex]

Substitute this value for y in the first equation to get

[tex] x-42=15 \iff x=15+42 \iff x = 57 [/tex]

Firstly, we need to write down the information given in the form of algebraic equations. We can represent our two unknown numbers, the greater and the lesser, as x and y respectively.

From the given information, we can form two equations. The first equation is from "the difference between the two numbers is 15", which gives us x - y = 15, where x is the larger number and y is the smaller one.

Also, we know that "If 8 is added to twice the greater number, the result is 4 less than 3 times the lesser number", this gives us the second equation: 2*x + 8 = 3*y - 4.

We now have a system of two equations that we can solve simultaneously:

1) x - y = 15
2) 2*x + 8 = 3*y - 4

To make it easier, let's multiply the first equation by 2, which gives us 2*x - 2*y = 30.

Now subtract the second equation (2*x + 8 = 3*y - 4) from the first (2*x - 2*y = 30), it yields: -2*y - 3*y = 30 - (-4 - 8).

This simplifies to -5y = 30 + 4 + 8, or -5*y = 42.

To get the value of y, divide by -5, therefore y = -42 / -5 = 42.

Now to find x, we can substitute y = 42 in the first equation (x - y = 15), so we get x = 42 + 15 = 57.

Hence, the greater number is 57 and the lesser number is 42.

Which expression is equivalent to m-n?

Answers

Answer:

D

Step-by-step explanation:

The equivalent expression of the expression m - n will be m + (-n). Then the correct option is D.

What is an equivalent expression?

The equivalent is the expression that is in different forms but is equal to the same value.

The definition of simplicity is making something simpler to achieve or grasp while also making it a little less difficult.

The expression is given below.

⇒ m - n

The equivalent expression of the expression m - n will be written as,

⇒ m - n

⇒ m + (-n)

The equivalent expression of the expression m - n will be m + (-n). Then the correct option is D.

More about the equivalent link is given below.

https://brainly.com/question/889935

#SPJ2

Starting at sea level, a submarine descended at a constant rate to a depth of −56 mile relative to sea level in 4 minutes.

What was the submarine's depth relative to sea level after the first minute?

Enter your answer in the box as a fraction in simplest form.

Answers

-56mi in 4 minutes is (56mi/4) in 1 minutes = 14mi/minute.

Therefore, the submarine was 14 miles below sea level after 1 minute.

Answer:

The submarine's depth relative to sea level after the first minute is -14 miles.

Step-by-step explanation:

Consider the provided information.

Starting at sea level, a submarine descended at a constant rate to a depth of −56 mile relative to sea level in 4 minutes.

This can be written as:

[tex]-56\ miles=4\ minutes[/tex]

To find the submarine's depth relative to sea level after the first minute, divide both the sides by 4.

[tex]\frac{-56}{4}\ miles=\frac{4}{4}\ minutes[/tex]

[tex]-14\ miles=1\ minutes[/tex]

Hence, the submarine's depth relative to sea level after the first minute is -14 miles.

a shipping company delivered 38728 letters and 41584 packages. write and solve an equation to find how many items the company delivered.

Answers

38,728 + 41,584 = 80,312

The company delivered 80,312 items.

given the replacement set {0,1,2,3,4} solve 4x - 5 = 11

Answers

4x - 5 = 11
4x = 11 + 5 = 16
4x = 16
Divide by 4 from both sides
X = 4

Charlie, Dan, and Ellie each made a paper chain. Charlie's was 9 1/2 feet long Dan's was 6 1/3 feet long, and Ellie's was feet long. When put together, how 8 1/3 long were the three chains?

Answers

24 1/6 but you should check the spelling your questions

Assuming Ellies was 8 /13 feet long

9 1/2 + 6 1/3 + 8 1/3 =

getting a common denominator of 6

9 3/6 + 6 2/6 + 8 2/6

23 7/6

24 1/6 feet


Solve: 3(1-2x) > 3-6x

Answers

3(1 - 2x) > 3 - 6x    use distributive property

(3)(1) + (3)(-2x) > 3 - 6x

3 - 6x > 3 - 6x    add 6x to both sides

3 > 3 FALSE

Answer: NO SOLUTION

miranda has 19 pieces of candy. she wants to give an equsl number of pieces to her 6 friends. how many pieces of candy will each friend get? write the answer as a mixed number.

Answers

19/6 or 3 1/6 or 3.17

6 * 3 + 1 = 19


the answer is

[tex]3 \frac{1}{6}[/tex]

Which statement is true about the end behavior of the graphed function? The graph and choices are attached.

Answers

The correct answer is A) as the x values go to positive infinity, then the graph goes to negative infinity.

We can tell this by looking at the graph values as x goes up. You'll notice, as we get higher and higher, the graph disappears down. This means it is heading towards negative infinity for the rest of the graph.

Answer:

The statement  which is true about the end behavior of the graphed function is:

As the x-value goes to positive infinity , the function's value go to minus infinity.       Step-by-step explanation:

We know that the end behavior of the function is the value where it approaches when x tends to plus infinity and minus infinity.

 From the graph of the function we see that the graph first decreases continuously and then it increases and again it decreases to minus infinity.

Also,

when x → -∞ we see that  f(x) → ∞

and when  x → ∞ then f(x) → -∞

As the function has opposite behavior in both the directions this means that the function is odd.

At x=0 the value of function is: -2

Write an equation of the line in point slope form that passes through the two given points (8,-8) slope 3

Answers

equation: y - k=m(x-h)
M: slope
given point: (h,k)
plug in
y- (-3)=3(x-8)
Final answer:

The equation of the line in point slope form that passes through the two given points is y + 8 = 3x - 24.

Explanation:

The equation of the line in point slope form that passes through the two given points (8,-8) and slope 3 can be found using the formula y - y1 = m(x - x1), where (x1, y1) represents one of the given points and m represents the slope. Plugging in the values, we get y - (-8) = 3(x - 8). Simplifying this equation gives us y + 8 = 3x - 24. This is the equation of the line in point slope form.

Learn more about equation of a line here:

https://brainly.com/question/21511618

#SPJ3

write an expression that uses partial products to multiply 8 x 64. Can your expression be written another way? Explain

Answers

we are asked to write an expression that uses partial products to multiply 8 and 64. In this case, we can break 8 into 2 x4 and 64 into 8x8. In this case, multiplying these factors equal to 512. Any factors will do actually since it will yield the same product.

PLZ HElP!!! Simplify 10 – 3x – 13 + 5x 3 – 3x 1 2x – 3 3 – 2x

Answers

the answer to the first part is 2x-3

Mr. Piper is driving Roddy and Scott home from school. They both want to ride in the front seat. How can he make a fair decision about who rides in the front seat?Select all of the correct answers.
A.Put each person's name on a separate piece of paper in a bag. Randomly draw the winning name.
B.Flip a coin twice. If both tosses are heads, Roddy wins. If one is heads and one is tails, Scott wins.
C.Roll a number cube. If it lands on 1 or 2, Roddy wins. If it lands on any other number, Scott wins.
D.Roll a number cube. If it lands on an even number, Roddy wins. If it lands on an odd number, Scott wins.

Answers

Answer:

A.Put each person's name on a separate piece of paper in a bag. Randomly draw the winning name; and D.Roll a number cube. If it lands on an even number, Roddy wins. If it lands on an odd number, Scott wins.

Step-by-step explanation:

In order for it to be a fair decision, both boys have to have an equal chance of being selected.

For choice A, drawing their names from a bag, both names are equally likely to be chosen; that makes this fair.

For choice B, there is 1 way to get both heads when flipping a coin.  There are 2 ways to get heads and tails when flipping a coin.  This gives Scott a greater chance, so this is not fair.

For choice C, there are 2 ways to get a 1 or a 2.  There are 4 ways to get anything else.  This gives Scott a greater chance, so this is not fair.

For choice D, there are 3 even numbers and 3 odd numbers.  Both boys have an equal chance, so this is fair.

Answer:

it a and d on any where

Step-by-step explanation:

HELP!!!!! The measure of the angle’s supplement is 20 degrees more than three times that of its complement. Find the measure of the angle described. The measure of the angle is?

Answers

By solving a linear equation, conclude that the measure of our angle is 55 degrees.

How to find the measure of the angle described?

We know that two angles A and B are supplementary if their measures add up to 180°, then:

A + B  = 180°

And two angles are complementary if their measures add up to 90°.

A + B = 90°

Now, let's define A as our angle, B as the supplement, and C as the complement, then we can write:

A + B = 180°

A + C = 90°

We know that B is 20° more than 3 times the complement, then we can write:

B = 20° + 3*C

Usuing the two equations above we can rewrite:

B = 180° - A

C = 90° - A

Replacing that above, we get:

(180° - A) = 20° + 3*( 90° - A)

We need to solve this linear equation for A.

180° - A = 20° + 270° - 3*A

3*A - A = 20° + 270° - 180°

2*A = 110°

A = 110°/2 = 55°

We conclude that the measure of our angle is 55 degrees.

Learn more about supplementary angles:

https://brainly.com/question/2046046

#SPJ1

1. Find the length of a rectangular lot with a perimeter of 124 feet if the length is two more than twice the width.

2. Find the length of a rectangular lot with a perimeter of 50 feet if the length is five more than the width.

Answers

ANSWER TO QUESTION 1


Let the width be
[tex]w[/tex]
units.



Twice the width will be

[tex]2w[/tex]

Two more than twice the width will be

[tex]2w + 2[/tex]



We were told that the length is 2 more than twice the width. This means that,

[tex]l = 2w + 2[/tex]


This implies that,

[tex]w = \frac{l - 2}{2} - - eqn(1)[/tex]


The formula for finding the perimeter of a rectangle is given by:


[tex]perimeter = 2w + 2l - - eqn(2)[/tex]




We substitute 124 for the perimeter and equation (1) into equation (2)



[tex]124 = 2( \frac{l - 2}{2} ) + 2l[/tex]


This implies that,

[tex]124 = l - 2 + 2l[/tex]

[tex]\Rightarrow 124 + 2 = l + 2l[/tex]



[tex]\Rightarrow 126 = 3l[/tex]




We divide both sides by 3 to obtain,


[tex]l = 42[/tex]

Therefore the length is 42 feet.





ANSWER TO QUESTION 2


Let the width be
[tex]w[/tex]


units.


Five more than the width will be


[tex]w + 5[/tex]


We were told that the length is 5 more than the width. This means that,


[tex]l = w + 5[/tex]


We make w the subject to obtain,


[tex]w = l - 5 - - eqn(1)[/tex]



The perimeter is given by,

[tex]perimeter = 2w + 2l - - eqn(2)[/tex]

We substitute 50 for the perimeter and equation (1) into equation (2)


[tex]50 = 2(l - 5) + 2l[/tex]

Dividing through by 2 gives,


[tex]25 = l - 5 + l[/tex]



[tex]\Rightarrow 25 + 5 = l + l[/tex]



[tex]\Rightarrow 30 = 2l[/tex]


We divide both sides by 2 to get,

[tex]l = 15[/tex]


Therefore the length is 15 feet.

write an equation that represents this comparison sentence. 32 is 8 times as many as 4

Answers

32=8*4 This is how the equation would be written. Hope I helped :)

The equation that represents this comparison sentence 32 is 8 times as many as 4 is [tex]32 = (8 \times 4)[/tex]

Times also means multiplication

8 times as many as 4 is expressed as [tex](8\times 4)[/tex]

If 32 is 8 times as many as 4, this is expressed as

Hence the equation that represents this comparison sentence 32 is 8 times as many as 4 is [tex]32 = (8 \times 4)[/tex]

Learn more here: https://brainly.com/question/5838836

A rental car agency charges $240 per week plus $0.25 per mile to rent a car. The charge for a minivan is $180 per week plus $0.40 per mile. After how many miles is the total charge for each vehicle the same?

Answers

Rental car agency charge:

Let's assume number of miles in as week as x miles

and total rent as R(x)

A rental car agency charges $240 per week plus $0.25 per mile to rent a car

so, we get equation as

[tex]R(x)=240+0.25x[/tex]

Minivan charge:

Let's assume number of miles in as week as 'x' hours

and total charge of minivan as M(x)

The charge for a minivan is $180 per week plus $0.40 per mile

so, we get

[tex]M(x)=180+0.40x[/tex]

now, we can set them equal

and then we can solve for x

[tex]240+0.25x=180+0.40x[/tex]

Subtract both sides by 0.25x

[tex]240+0.25x-0.25x=180+0.40x-0.25x[/tex]

[tex]240=180+0.15x[/tex]

Subtract both sides by 180

[tex]240-180=180+0.15x-180[/tex]

[tex]60=0.15x[/tex]

divide both sides by 0.15

and we get

[tex]x=400 miles/tex]............Answer


Final answer:

The total charge for each vehicle, a car and a minivan, is the same when 400 miles are driven.

Explanation:

The subject you're dealing with here is algebra, specifically, finding the point where two linear functions intersect which shows when the cost of renting the two different vehicles will be the same.

Let's use the formula for the cost of each vehicle, where C is the total cost, W is the flat weekly charge, M is the price per mile, and X is the number of miles driven:

For the car: C = $240W + $0.25M X

For the minivan: C = $180W + $0.40M X

Set these two equations equal to each other to solve for X, the number of miles driven when the two costs are equal:

$240W + $0.25M X = $180W + $0.40M X

Subtracting $180W from both sides and $0.25M X from both sides, you get:

$60W = $0.15M X

Finally, divide by $0.15M to solve for X:

X = $60W/$0.15M = 400 miles

Therefore, the total charge for each vehicle is the same when 400 miles are driven.

Learn more about Algebra here:

https://brainly.com/question/24875240

#SPJ3

Other Questions
Why does Galileo believe God approves of his discoveries? God does not want Galileo to believe in him. God created the stars, so he created astronomy. God showed Galileo the workings of the universe. God gave humanity the ability to make such discoveries. Identify the level of organization. a. Group of bats living in a cave ________________ b. Red-eyed tree frog _______________ c. Insects, fish and algae in a lake _________________ d. An ocean ______________ Use the polynomial remainder theorem to evaluate the polynomial for the given value.f(x)=3x^32x^23x+18What is the value of f(1) ? If you want to say you are going to a wedding in Spanish, which word should you use? Which methods did Georgia use to distribute land in the late 1700s and early 1800s? I need help with 57 and 58. Thank you in advance What is the name of the document signed by King John that limited power of the English Monarchy and provided rights to the nobles? Bob is making mini fondant cakes for next bake sale each cake costs bob $1.80 to make if he sells the cakes for $3.00 each how many will he have to sell to make a profit of exactly $36.00 please help me answer Mary mixes 11/12 oz of red paint with 1 3/4 oz of white paint.How many ounces of paint does Mary mix?A. 123 ozB .156 ozC. 178 ozD .223 oz What was the primary reason for the English colonization of Jamestown in 1697 near the James river Box A contains 53 cubes and has a mass of 1760 grams. Box B contains 18 cubes and has a mass of 1620 grams. The mass of box A is the same as the mass of box B. Every cube has the same mass. [EVALUATE] Throughout the story, Tom Struggles with the fear that he will die young. How does Tom resolve this conflict at the end of the story? Do you find this resolution effective? Explain.(NOTE) You must have read "The Deep" Short Story by Anthony Doerr in order to answer this question. Sam is looking for a cell phone plans.A local company offers a monthly plan for $58.95. The company is having a sale and offering a discount for $4.75 off the monthly plan.Sam says the new cost is $11.45. Explain sams error and find the correct new cost The height of a baseball thrown from the catcher to first base is modeled by the function h(t) = 0.09t2 + 0.72t + 6, where h is the height of the ball measured in feet and t is the time since being thrown, measured in seconds. The ball is in the air for 10 seconds before being caught. What's the height of the ball at 10 seconds? Duane bought 63 3/4 inches of chain for an art project. How many 15 inch chains can he make from it? Write a short narrative about a real or imagined event. Your narrative can be free-form or structured like epic poetry, but youll want to have a clear beginning and end that includes a conflict. If you have trouble starting your story, use the writing prompt below. Writing prompt: She looked up at a sky laden with angry clouds, and she A box contains 4 red and 3 blue poker chips. Three chips are pulled random. What is the probability that all are red with a replacement Martin Luther King, Jr. _______. Which sulfuric exhibits the highest albedo measurement SandForest coverBare soilFresh snow When people get their hair chemically straightened, one chemical is put on the hair to break the disulfide bond that give the hair strands their shape and a second chemical is used to reform the disulfide bonds to hold the hair in a new position. what level of protein is affected by these processes. why doesnt the hair stay straight forever after treatment